Avaliação da espessura do esmalte em dentes posteriores permanentes em pacientes adultos com tomografia computadorizada de feixe cônico - Biesdorf, Renata Marques (2022)
Introduction: The interproximal reduction (IPR) technique is a frequente procedure in orthodontic practice, in which part of the dental enamel of the mesial and distal areas is removed, in order to create space. For the IPR to be performed safely, it is important to estimate the actual thickness of the enamel. Purpose: The aim of this study is to evaluate the enamel thickness of maxillary and mandibular premolars and molars in different dental occlusions in CBCT, in adults, in two groups with no history of previous orthodontic treatment. Materials and Methods: A total of 151 teeth, premolars and mandibular and maxillary molars, were evaluated in high quality CBCT, obtained by the PreXion 3D tomographer and data such as age, sex and evaluated teeth were recorded. Teeth of 14 patients (5 men; 9 women) aged between 22 and 56 years (mean = 39 years) were studied and only sound teeth, without the presence of occlusal wear and restorations were selected for evaluation. Results: There was a statistically significant difference in the mesial and lingual thickness, which presented higher values in the maxillary molars than in the mandibular premolars. Regarding distal enamel thickness, molars were thicker than premolars. There was no significant difference in terms of gender between the groups of teeth analyzed. When comparing the two age groups, there were statistically significant differences in enamel thickness on the mesial and distal surfaces. Conclusions: The posterior teeth have such a thickness of enamel, which allows the performance of interproximal reduction in this region.